Absorption and tolerability of taste‐masked hydrocortisone granules in neonates, infants and children under 6 years of age with adrenal insufficiency. (7th September 2017) - Neumann, Uta; Whitaker, Martin J.; Wiegand, Susanna; Krude, Heiko; Porter, John; Davies, Madhu; Digweed, Dena; Voet, Bernard; Ross, Richard J.; Blankenstein, Oliver
Summary: Objectives: There is no licensed, dose‐appropriate formulation of hydrocortisone for children with adrenal insufficiency (AI) and patients rely on compounded adult medication. The aim of this study was to evaluate the absorption, palatability and safety of Infacort ®, an immediate‐release, granule formulation of hydrocortisone with taste masking. Study design: Single site with satellites attended by a "flying" doctor from investigator site. Open‐label, single‐dose study in three consecutive child cohorts (n = 24) with AI; Cohort 1, children aged 2 to <6 years (n = 12); Cohort 2, infants aged 28 days to <2 years (n = 6); Cohort 3, neonates aged 1 to <28 days (n = 6). Methods: Fasted children were given a single dose of Infacort ® as dry granules administered directly from a capsule or spoon followed by a drink. The primary end‐point was the maximum serum cortisol concentration up to 240 minutes after Infacort ® administration. Secondary end‐points were palatability and adverse events (AEs). Results: All children showed an increase in cortisol above baseline after Infacort ® ( P < .0001), with geometric mean ± SD cortisol concentration at 60 minutes of 575.8 ± 299.5 nmol L −1 . There was no failure in administration of Infacort ®, and 95.5% of parents/carers preferred Infacort ® to their child's current medication. In 7 children who completed the palatability questionnaire, 80% of responses were very good or neutral, and 20% were adverse. No serious or severe treatment‐emergent AEs were reported. Conclusions: Infacort ® is well tolerated, easy to administer to neonates, infants and children and shows good absorption, with cortisol levels at 60 minutes after administration similar to physiological cortisol levels in healthy children.